2019
DOI: 10.31223/osf.io/vqkds
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Revised timing of Cenozoic Atlantic incursions and changing hinterland sediment sources during southern Patagonian orogenesis

Abstract: New detrital zircon U-Pb geochronology data from the Cenozoic Magallanes-Austral Basin in Argentina and Chile ~51°S establish a revised chronostratigraphy of Paleocene – Miocene foreland synorogenic strata and document the rise and subsequent isolation of hinterland sources in the Patagonian Andes from the continental margin. The upsection loss of zircons derived from the hinterland Paleozoic and Late Jurassic sources between ca. 60-44 Ma documents a major shift in sediment routing due to Paleogene orogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
(65 reference statements)
1
4
0
1
Order By: Relevance
“…An error-weighted mean of the youngest coherent zircon population (n = 7) yields a calculated MDA of 24.6 ± 0.5 Ma (2σ). This age overlaps with the calculated MDA of 24.3 ± 0.6 Ma (2σ) from the stratigraphically lower RT28DZ6 from Fosdick et al (2019) at the base of the Río Guillermo Formation, which does not suffer from similarly low zircon fertility.…”
Section: Detrital Zircon U-pb La-icp-ms Geochronologysupporting
confidence: 80%
See 4 more Smart Citations
“…An error-weighted mean of the youngest coherent zircon population (n = 7) yields a calculated MDA of 24.6 ± 0.5 Ma (2σ). This age overlaps with the calculated MDA of 24.3 ± 0.6 Ma (2σ) from the stratigraphically lower RT28DZ6 from Fosdick et al (2019) at the base of the Río Guillermo Formation, which does not suffer from similarly low zircon fertility.…”
Section: Detrital Zircon U-pb La-icp-ms Geochronologysupporting
confidence: 80%
“…As part of a regional study on the kinematic history of faulting and sedimentaton across the Patagonian Andes, Fosdick et al (2011) reported a zircon U-Pb SHRIMP age from an interbeded tuff at the top of the Río Guillermo Formation, suggesting the top of the unit was as young as 21.7 Ma. More recently, Fosdick et al (2019) provided new estimates on the timing of sedimentaton for the whole Cenozoic basin succession in our study area -including the lower formationnal boundary of the Río Guillermo Formation -based on detrital zircon U-Pb geochronological data. These data establish a latest Chattian through Aquitanian age (∼24.3-21.7 Ma) for the Río Guillermo Formation and support the interpretation of contemporaneous deposition with previously recongnized faulting stages within the fold-and-thrust belt (later Stage IV and early Stage V faulting of Fosdick et al, 2011Fosdick et al, , 2019.…”
Section: Previous Work On Río Guillermo Formationmentioning
confidence: 99%
See 3 more Smart Citations